Luminescent Eu(iii) hybrid materials for sensor applications - Barja, Beatriz Carmen (2008)
In this work we use the sol–gel technique to develop different luminescent Eu(III) porous materials from a bis(trialkoxysilyl) organic precursor synthesized from the amide of the DPA (2,6-pyridinedicarboxylic acid) with APTES (aminopropyltriethoxysilane) in the presence or absence of the non-ionic surfactant F-127. The emission spectrum of the luminescent Eu(III) complex obtained was used to sense and compare the environment of the lanthanide in the amorphous matrices as well as the accessibility of the material by means of the quenching of its luminescence by Cu(II). Solid devices were built to test and compare their performances as potential sensors of Cu(II) in terms of the values of the Stern–Volmer constants in the quenching experiments. Templated materials with F127 showed the best response (KSV = 1.2 105 M-1) when compared with the results obtained for the non-templated ones at different synthesis conditions permitting the in situ detection of Cu(II) in solution down to the 0.05 ppm levelIII) porous materials from a bis(trialkoxysilyl) organic precursor synthesized from the amide of the DPA (2,6-pyridinedicarboxylic acid) with APTES (aminopropyltriethoxysilane) in the presence or absence of the non-ionic surfactant F-127. The emission spectrum of the luminescent Eu(III) complex obtained was used to sense and compare the environment of the lanthanide in the amorphous matrices as well as the accessibility of the material by means of the quenching of its luminescence by Cu(II). Solid devices were built to test and compare their performances as potential sensors of Cu(II) in terms of the values of the Stern–Volmer constants in the quenching experiments. Templated materials with F127 showed the best response (KSV = 1.2 105 M-1) when compared with the results obtained for the non-templated ones at different synthesis conditions permitting the in situ detection of Cu(II) in solution down to the 0.05 ppm levelIII) complex obtained was used to sense and compare the environment of the lanthanide in the amorphous matrices as well as the accessibility of the material by means of the quenching of its luminescence by Cu(II). Solid devices were built to test and compare their performances as potential sensors of Cu(II) in terms of the values of the Stern–Volmer constants in the quenching experiments. Templated materials with F127 showed the best response (KSV = 1.2 105 M-1) when compared with the results obtained for the non-templated ones at different synthesis conditions permitting the in situ detection of Cu(II) in solution down to the 0.05 ppm levelII). Solid devices were built to test and compare their performances as potential sensors of Cu(II) in terms of the values of the Stern–Volmer constants in the quenching experiments. Templated materials with F127 showed the best response (KSV = 1.2 105 M-1) when compared with the results obtained for the non-templated ones at different synthesis conditions permitting the in situ detection of Cu(II) in solution down to the 0.05 ppm levelII) in terms of the values of the Stern–Volmer constants in the quenching experiments. Templated materials with F127 showed the best response (KSV = 1.2 105 M-1) when compared with the results obtained for the non-templated ones at different synthesis conditions permitting the in situ detection of Cu(II) in solution down to the 0.05 ppm levelKSV = 1.2 105 M-1) when compared with the results obtained for the non-templated ones at different synthesis conditions permitting the in situ detection of Cu(II) in solution down to the 0.05 ppm levelin situ detection of Cu(II) in solution down to the 0.05 ppm level.